MEMBANGUN KESADARAN LITERASI DIGITAL, MELALUI BIJAK BERMEDIA SOSIAL DAN INTERNET - Suworo Suworo; Giosanjora Giosanjora; Monica Aprillina Dwiyanti; Piaggio Bela Nagara (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2026)
The development of digital technology has made it easier for students to access information and communicate via the internet. However, this convenience has not been fully accompanied by a good understanding of digital literacy. Many students use social media and the internet without realizing the risks of spreading misinformation, excessive social media use, and threats to personal data security. This Community Service activity aims to improve students' understanding of digital literacy through education on the wise use of social media and the implementation of healthy internet practices. The activity was held at Muhammadiyah 25 Pamulang High School, involving eleventh-grade students. The implementation method included material delivery, interactive discussions, question-and-answer sessions, and simple practices related to digital security. The material presented included an introduction to digital literacy, how to recognize hoaxes, social media ethics, managing internet usage, and basic steps for maintaining digital account security. The results of the activity showed an increase in students' understanding of the importance of digital literacy. Students began to be able to sort the information they received, demonstrated a wiser attitude in using social media, and understood the importance of maintaining personal data security. This activity is expected to help foster healthier and more responsible digital habits among students.